Evidence for contemporary and historical gene flow between guppy populations in different watersheds, with a test for associations with adaptive traits. Issue 8 (29th March 2019) - Blondel, Léa; Baillie, Lyndsey; Quinton, Jessica; Alemu, Jahson B.; Paterson, Ian; Hendry, Andrew P.; Bentzen, Paul
Abstract: In dendritic river systems, gene flow is expected to occur primarily within watersheds. Yet, rare cross‐watershed transfers can also occur, whether mediated by (often historical) geological events or (often contemporary) human activities. We explored these events and their potential evolutionary consequences by analyzing patterns of neutral genetic variation (microsatellites) and adaptive phenotypic variation (male color) in wild guppies ( Poecilia reticulata ) distributed across two watersheds in northern Trinidad. We found the expected signatures of within‐watershed gene flow; yet we also inferred at least two instances of cross‐watershed gene flow—one in the upstream reaches and one further downstream. The upstream cross‐watershed event appears to be very recent (41 ± 13 years), suggesting dispersal via recent flooding or undocumented human‐mediated transport. The downstream cross‐watershed event appears to be considerably older (577 ± 265 years), suggesting a role for rare geological or climatological events. Alongside these strong signatures of both contemporary and historical gene flow, we found little evidence of impacts on presumably adaptive phenotypic differentiation, except perhaps in the one instance of very recent cross‐watershed gene flow. Selection in this system seems to overpower gene flow—at least on the spatiotemporal scales investigated here. Abstract : We investigated the population genetic structure of two watersheds in Trinidad. We found that population structured mainly within watersheds, but also surprisingly pointed out two locations where gene flow happened across watersheds, with one recent event and one older. We then compared structure in neutral genetic markers with structure in one adaptive trait—male color, but found no association between color and either geographic proximity or timing of gene flow.